2013
DOI: 10.1111/dme.12236
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of self‐monitoring of blood glucose in patients with Type 1 diabetes: a multi‐centre study in Brazil

Abstract: The majority of our patients (88.5%) performed three or more self-monitoring tests daily, with more frequent testing reported by females, younger patients, those on intensive insulin regimens and of higher socio-economic status. No additional benefit was found in patients who performed self-monitoring more than four times daily. The diabetes care team must improve patients' education regarding self-monitoring of blood glucose and its benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
(73 reference statements)
0
13
0
2
Order By: Relevance
“…Insulin represented 26.1% of expenses. Further analysis of the Cobas study also showed that more frequent SMBG (up to four tests per day) was associated with improved HbA 1c levels [25].…”
Section: Expensive Blood Glucose Monitoringmentioning
confidence: 88%
“…Insulin represented 26.1% of expenses. Further analysis of the Cobas study also showed that more frequent SMBG (up to four tests per day) was associated with improved HbA 1c levels [25].…”
Section: Expensive Blood Glucose Monitoringmentioning
confidence: 88%
“…Furthermore, individual health behaviour may influence various healthcare outcomes . Persons with Type 1 diabetes and higher socio‐economic status, for example, measure their blood glucose more often than those of lower socio‐economic status . Thus, inequalities in short‐term healthcare outcomes cannot be explained by one underlying factor, but are very likely caused through a multifactorial process.…”
Section: Discussionmentioning
confidence: 99%
“…The data collection methods have been described previously [19-21]. The inclusion criteria consisted of patients with a diagnosis of T1D by a physician.…”
Section: Methodsmentioning
confidence: 99%